Cross-Cultural Adaptation and Psychometric Evaluation of the Persian Version of the Caring Behaviors Assessment Tool Nursing Version-Short Form - Faezeh Yousefi BSc; Ali Asghar Parhizkari BSc; Hamid Sharif-Nia PhD; Saeed Ghasempour BScN; Ali Abbasi PhD (SAGE Open Nursing)
Introduction Caring is an integral part of the nursing profession, often viewed as an abstract and immeasurable behavior. However, caring behaviors can be measured and evaluated, ultimately improving care outcomes and practices. To accomplish this, a valid and reliable tool for measuring caring behaviors is essential. One such tool is the Caring Behaviors Assessment Tool Nursing Version-Short Form (CBAN-SF), which has not yet been translated and psychometrically evaluated in Iran. Objective This study aimed to evaluate the psychometric properties of the Persian version of the CBAN-SF. Methods A methodological study was conducted at two hospitals affiliated with Shahroud University of Medical Sciences using a cross-sectional approach. The CBAN-SF was translated into Persian following the forward–backward procedure outlined by the World Health Organization (WHO) guidelines. The validity (including face, content, and construct) and reliability (encompassing internal consistency and stability) of the Persian version of the CBAN-SF were assessed. In order to assess construct validity, 400 eligible clinical nurses were included in the study. The first 200 samples were used to conduct exploratory factor analysis (EFA), while the second 200 samples were used to conduct confirmatory factor analysis (CFA). Reliability was gauged through Cronbach's alpha coefficient, MacDonald's omega coefficient for internal consistency, and intraclass correlation coefficient for stability. Results The assessment of content validity and EFA resulted in the removal of one item and six others, leaving a final set of 20 items. These were divided into four factors: “dignified care,” “expression of feelings,” “self-sufficiency and self-belief,” and “patient-centered care,” which together explained 56.82% of the total variance. The CFA demonstrated that the model closely matched the observed data. Furthermore, each subscale exhibited strong internal consistency and stability. Conclusion It can be concluded that the Persian version of the CBAN-SF shows adequate validity and reliability in evaluating the caring behavior of clinical nurses.